Study of Phase Advance Angle Control (PAAC) Technique for Brushless DC (BLDC) Motor - Yahaya, Nor Zaihar (2013)
The brushless DC (BLDC) motor is recognized by the linear speed to voltage and torque to current respectively. It possesses fast dynamic response and high power density with high proportion of torque in spite of small size drive. However, it is difficult for conventional BLDC motor drives where they require wide range of operating speed. This is due to the torque and speed response characteristics at high speed operating mode in which deteriorated by the motor inductance components in stator winding. Phase advance angle control (PAAC) technique is used to control the phase current and improve torque and speed responses in high speed operating mode. This paper discusses the design of high-speed lossless BLDC motor using simulation where the compatible phase advance motor drive is developed. The results are then compared with laboratory proof for validation.